2017
DOI: 10.1103/physreva.95.042505
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent density-functional theory for strongly interacting electrons

Abstract: We consider an analytically solvable model of two interacting electrons that allows for the calculation of the exact exchange-correlation kernel of time-dependent density functional theory. This kernel, as well as the corresponding density response function, is studied in the limit of large repulsive interactions between the electrons and we give analytical results for these quantities as an asymptotic expansion in powers of the square root of the interaction strength. We find that in the strong interaction li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…The ASCE kernel was shown to reproduce the so-called zeropoint oscillation part of the spectrum. The attainment of this exact result shows that the ASCE kernel becomes exact in the this regime as we also concluded from earlier work [7]. However, most current interest in molecular dissociation in chemistry is devoted to the complementary regime of large bond distance at intermediate interaction strength.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The ASCE kernel was shown to reproduce the so-called zeropoint oscillation part of the spectrum. The attainment of this exact result shows that the ASCE kernel becomes exact in the this regime as we also concluded from earlier work [7]. However, most current interest in molecular dissociation in chemistry is devoted to the complementary regime of large bond distance at intermediate interaction strength.…”
Section: Discussionsupporting
confidence: 82%
“…To correct these problems within the present formalism a natural way to proceed would be include ZPE and higher order kernels in the expansion of the Hxc kernel as was done in Ref. [7]. However, that work showed that the extra terms lead to worse approximation than just the ASCE approximation for low interaction strengths, as is typical for an asymptotic expansion.…”
Section: Lowest Excitation Energymentioning
confidence: 99%
See 3 more Smart Citations